Depression, anxiety, and health related quality of life among colorectal cancer survivors - Aminisani, Nayyereh; Nikbakht, Hosseinali; Jafarabadi, Mohammad Asghari; Shamshirgaran, Seyed Morteza (Journal of Gastrointestinal Oncology; Vol 8, No 1 (February 22, 2017): Journal of Gastrointestinal Oncology, 2017)
Background: The aim of this study was to examine the relationship between psychological distress and quality of life (QOL) dimensions in colorectal cancer (CRC) patients. Methods: This cross-sectional study was conducted in the North of Iran. A total of 157 CRC survivors were selected from the registry database and included in this study. Psychological distress was measured using the Hospital Anxiety and Depression Scale (HADS) and QOL was estimated using the European Organization for Research and Treatment of Cancer Quality-of-Life Questionnaire C30 (EORTC QLQ C-30). The association between the patients’ emotional functioning (EF) score on EORTC QLQ-C30 and their HADS scores was analysed through multiple linear regression. Results: In statistical terms, there were significantly negative relationships between EF and HADS-A (anxiety), and between HADS-D (depression) and HADS-T (total score). However, compared with HADS-A, the correlation between HADS-D and other QOL dimensions was significantly higher. By the same token, depression rather than anxiety was more strongly associated with reduced QOL. Conclusions: The EF dimension of the EORTC QLQ-C30 predominantly assesses anxiety; however, depression has a stronger impact on the global QOL of patients than anxiety. Therefore, the use of an additional instrument is recommended for the assessment of depression in outpatients with CRC.